Addressing the challenges that affect COVID-19 prevention in the rural areas of Abia State, Nigeria - Enwereji, E. E.; Ezeama, M. C. (International Journal Of Community Medicine And Public Health, 2020)
Background: Using directives have been the standard approach of changing public behavior. But studies have shown that directives fail because people hate being told what to do. Telling individuals to use limited resources and other social amenities in rural areas to prevent coronavirus disease 2019 (COVID-19) infection may lead to skepticism in practice of public health recommendations on COVID-19 prevention. Even non-availability of basic hand washing facilities (soap and clean water) which form fundamental mechanism to prevent COVID-19 can expose people to infection. Study assesses factors and conditions that influence the practice of Center for disease control (CDC) preventive measures against COVID-19 in rural areas. Methods: This is a qualitative study that utilized information from 36 health care professionals under the aegis of committee for COVID-19 prevention. These committee members are working together in partnership with state government to provide services to control, prevent and cushion effects of COVID-19 pandemic. Results: Findings from 36 health care professionals made up of 10 (27.8%) females and 26 (72.2%) males showed that factors such as denial of existence of the virus, labeling virus as only urban limited, poor knowledge of mode of transmission, terming virus as ploy politicians use to siphon resources meant for rural development contributed to non-observation of CDC guidelines for COVID-19 prevention. Conclusions: Denying existence of COVID-19 and not observing CDC guidelines will increase community transmission thereby, expose people in communities to infection. Therefore, education is needed to enlighten people in communities on benefits of observing CDC guidelines.